Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1016/0020-7292(92)90334-f
|View full text |Cite
|
Sign up to set email alerts
|

A new nonsurgical technique for termination of intrauterine pregnancy associated with large multiple uterine leiomyomas

Abstract: Medical termination of a first trimester intrauterine pregnancy associated with large and multiple leiomyomas posed a unique problem because the sac was inaccessible per vaginum for surgical or vacuum evacuation. The use of prostaglandins was contraindicated due to a past history of bronchial asthma. But intraamniotic and intraplacental instillation of methotrexate, 25 mg at each site, under ultrasound guidance resulted in termination of pregnancy. No side effects or complications were observed after the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Recently, several authors have reported the use of methotrexate and misoprostol to terminate pregnancy. [6][7][8] Creinin and Vittinghoff used misoprostol either alone or in combination with methotrexate up to 56 days from the last menstrual period. 9 They reported that with the combination of methotrexate and misoprostol, 90 percent of their subjects had complete abortions.…”
mentioning
confidence: 99%
“…Recently, several authors have reported the use of methotrexate and misoprostol to terminate pregnancy. [6][7][8] Creinin and Vittinghoff used misoprostol either alone or in combination with methotrexate up to 56 days from the last menstrual period. 9 They reported that with the combination of methotrexate and misoprostol, 90 percent of their subjects had complete abortions.…”
mentioning
confidence: 99%
“…Studies focussing on this mode of treatment are few. Buckshee and Dhond [5] reported successful termination of early intrauterine pregnancy with a huge leiomyoma by intraamniotic and intraplacental MTX [5]. Lui et al compared efficacy and safety of local and systemic MTX in CSE.…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of methods by which to induce late TOP, which can include fetal intracardiac injection of other substances (such as a fibrin adhesive [13] or lidocaine [14]), other routes of injection (for example intracranial injection [15] or intraplacental injection of methotrexate [16]), intraumbilical air embolism [17], intra-amniotic digoxin [18], as well as surgical methods (such as radiofrequency ablation and cord occlusion). Whilst we do not expect significant differences in imaging features with different substances injected via an intracardiac route, this was not formally assessed in our study.…”
Section: Discussionmentioning
confidence: 99%